Aerostatic and aerodynamic modules of a hybrid buoyant aircraft: an analytical approach - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Syed Mohamed Ali, Jaffar (IIUM Press, 2015)
An analytical approach is essential for the estimation of the requirements of aerodynamic and aerostatic lift for a hybrid buoyant aircraft. Such aircraft have two different modules to balance the weight of aircraft; aerostatic module and aerodynamic module. Both these modules are to be treated separately for estimation of the mass budget of propulsion systems and required power. In the present work, existing relationships of aircraft and airship are reviewed for its further application for these modules. Limitations of such relationships are also discussed and they provide a starting point for better understanding of design methodology of such aircraft.